A study of thyroid function in premenopausal and postmenopausal women of Dibrugarh town, Assam, India - Bordoloi, Gitartha; Jahan, Wasima (International Journal of Research in Medical Sciences, 2018)
Background: Ageing process can cause some changes in body system controlling mechanism. Consequently thyroid hormone levels may show variations reflected by TSH level in elderly people, more so in females. Methods: Serum TSH level were measured in 304 apparently healthy females of Dibrugarh town, Assam. Unbound T3 and T4 were measured if TSH level was abnormal. TSH levels were compared among different age groups. Results: The prevalence of hypothyroidism was found to be 8.2% in premenopausal and 12.7% in postmenopausal women. There were more cases of subclinical hypothyroidism than clinical hypothyroidism. Difference of Mean± SEM of TSH level in these two groups was significant though there was no correlation between age and TSH level. Conclusions: The study reveals decreasing thyroid function in postmenopausal female population of Dibrugarh town.